Pengaruh Penerapan Metode Demonstrasi dan Motivasi Belajar Terhadap Kemampuan Membaca Al-Qur`an Secara Tartil Siswa SMA Islam Al-Azhar 5 Kota Cirebon - Isyraq Fauziyyah (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2021)
This thesis examines the effect of the application of the demonstration method and learning motivation on the students' ability to read the Qur'an in Tartan Islamic high school Al-Azhar 5 Cirebon City. This research is a descriptive quantitative research. a balance between: a) Human relations with Allah SWT b) Human relations with fellow humans c) Human relations with oneself d) Human relations with other creatures and their environment. The scope of Islamic Religious Education subject matter includes five main elements, namely: a) al-Qur'an b) Aqidah c) Shari'ah d) Morals e) Date. In this research, the writer will focus on learning Al-Qur'an education using demonstration method. This has the aim that by implementing the demonstration method in learning al-Qur'an education, it can improve the ability of students to read the al-Qur'an. To achieve the maximum learning goals and objectives, a good delivery method is needed, which is commonly called a method. Respondents' responses regarding the use of the demonstration method in the Al-Qur`an Education subject were sufficient. This is evident from the average results of the application of the demonstration method, most of which are in the good category with an average percentage of achievement of 78.75% because it is in the 75% - 100% interval. As for the relationship between the application of the demonstration method in increasing learning motivation and the ability to read Al-Qur`an in tartile manner at AL-Azhar 5 Senior High School in Cirebon, there is a moderate correlation. This can be proven from the calculation of the correlation coefficient with a value of 0.696 which is in the range 0.40-0.70. The magnitude of the influence of the demonstration method on tartiles was 48.44%, while the remaining 51.56% was influenced by other factors not examined. Demonstration method was found to significantly improve artillery because the